2017
DOI: 10.1186/s12876-017-0665-y
|View full text |Cite
|
Sign up to set email alerts
|

p53 expression in patients with ulcerative colitis - associated with dysplasia and carcinoma: a systematic meta-analysis

Abstract: BackgroundTumor suppressor gene p53 expression has been reported in patients with ulcerative colitis (UC). However, the correlation between p53 expression and UC remains controversial. The aim of this meta-analysis was to investigate the association between p53 expression and different pathological types of UC.MethodsPublications were searched in the PubMed, Embase, EBSCO, Wangfang, and CNKI databases. The overall odds ratios (ORs) and their corresponding 95% confidence intervals (95% CIs) were summarized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
(45 reference statements)
1
17
0
3
Order By: Relevance
“…As a tumor suppressor, p53 plays a crucial role in the cell cycle, apoptosis and senescence, and is highly expressed in patients with UC-CRC. 42 In our study, the expression of p53 was significantly enhanced by AOM/DSS in mice. p53 is normally low-expressed in cells and rapidly degraded.…”
Section: Discussionsupporting
confidence: 51%
“…As a tumor suppressor, p53 plays a crucial role in the cell cycle, apoptosis and senescence, and is highly expressed in patients with UC-CRC. 42 In our study, the expression of p53 was significantly enhanced by AOM/DSS in mice. p53 is normally low-expressed in cells and rapidly degraded.…”
Section: Discussionsupporting
confidence: 51%
“…The cause of UC-CRC is considered to be the accumulation of inflammatory changes associated with colonic epithelial injury, repair, and regeneration, and the disease is believed to occur in an inflammation-dysplasiacarcinoma sequence. To ascertain tumor aggressiveness in the context of this sequence, p53 expression has been used (3,4), However, there is a need for other biomarkers that can predict the degree of tumor malignancy.…”
mentioning
confidence: 99%
“…Lu et al have shown in their meta-analysis that p53 expression was positive in cases of UC associated with carcinoma and dysplasia (5). The frequency of anti-p53 Abs in patients with tumors is strictly correlated with the frequency of p53 mutations (16).…”
Section: Discussionmentioning
confidence: 99%
“…These mutations result in the accumulation of the p53 protein, which causes p53 overexpression in tissue. There have been many reports of p53 overexpression in cases of ulcerative colitisassociated colorectal cancer (CAC) (5).…”
mentioning
confidence: 99%